SNAREs — engines for membrane fusion - Jahn, Reinhard; Scheller, Richard H. (Nature reviews. Molecular cell biology, 2006)
Key Points SNAREs (soluble N -ethylmaleimide-sensitive factor attachment protein receptors) form a superfamily of small fusion proteins that are each characterized by a conserved domain termed the SNARE motif, a membrane-anchor domain and a more variable N-terminal domain. SNAREs mediate membrane fusion through the spontaneous assembly of four complementary SNARE motifs. The assembly process leads to a tight connection between the fusing membranes and initiates membrane fusion. SNARE assembly and disassembly are complex multistep reactions that are subject to several layers of regulation. These steps include: the control of SNARE reactivity in the membrane; the formation of SNARE subcomplexes that function as acceptors for the final assembly step; trans -SNARE complexes that bridge the opposing membranes before fusion; and the disassembly of SNARE complexes by the AAA+ (ATPases associated with various cellular activities) protein NSF ( N -ethylmaleimide-sensitive factor). Accessory proteins, such as SM (Sec1/Munc18-related) proteins, synaptotagmins and complexins, regulate parts of the SNARE cycle. Some of these proteins are conserved and seem to function on many SNAREs, whereas others seem to be specific for a few SNAREs. In most cases, their mechanism of action is only partially clear. SNAREs function in all fusion reactions of the secretory pathway. Some function in only one trafficking step, whereas others are less specialized, which provides a healthy mix of robustness and flexibility. Since their discovery in the late 1980s, SNARE proteins have been recognized as key components of protein complexes that drive intracellular membrane fusion. Despite considerable sequence divergence, their mechanism seems to be conserved and is adaptable for diverse fusion reactions. Since the discovery of SNARE proteins in the late 1980s, SNAREs have been recognized as key components of protein complexes that drive membrane fusion. Despite considerable sequence divergence among SNARE proteins, their mechanism seems to be conserved and is adaptable for fusion reactions as diverse as those involved in cell growth, membrane repair, cytokinesis and synaptic transmission. A fascinating picture of these robust nanomachines is emerging.